Fatal Disseminated Tuberculosis in Vaccinated Children with Failed BCG Scar Formation: A Clinical-Pathological Correlation and Immunological Review - Delicia Rudy; Prisillia Brigitta; I Kadek Suarca (HM Publisher, 2026)
Background: The Bacillus Calmette-Guérin (BCG) vaccine remains the cornerstone of preventative strategies against severe pediatric tuberculosis (TB), specifically disseminated forms such as miliary TB and tuberculous meningitis (TBM). While the formation of a cutaneous scar is historically viewed as a surrogate marker for successful vaccine uptake and delayed-type hypersensitivity (DTH), its absence is often clinically overlooked. This study investigates the correlation between the lack of BCG scarring, immunological anergy, and fatal disseminated disease outcomes. Case presentation: We report a clinical-pathological analysis of two pediatric patients admitted to a tertiary care center in Indonesia. Case 1, an 11-month-old male vaccinated at birth, presented with status epilepticus and was diagnosed with Probable TBM Stage III. Despite vaccination, he lacked a BCG scar and exhibited Tuberculin Skin Test (TST) anergy (0 mm). Case 2, a 2-year-8-month-old female vaccinated at birth, presented with Type 1 respiratory failure due to severe miliary TB. She demonstrated profound wasting and TST anergy (0 mm). Both patients succumbed to the disease (Day 9 and Day 14, respectively) despite aggressive management. Conclusion: The absence of a BCG scar in vaccinated children serves as a critical clinical indicator of